INHIBITORY EFFECT OF SAPONINS AND POLYSACCHARIDES FROM RADIX RANUNCULI TERNATI ON HUMAN GASTRIC CANCER BGC823 CELLS - Niu, Lidan; Zhou, Yingfeng; Sun, Bing; Hu, Junling; Kong, Lingyu; Duan, Sufang (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The effects of different Radix ranunculi ternati extracts on human gastric cancer BGC823 cells were investigated, different methods were used to extract the saponins and polysaccharides from Radix ranunculi ternati, and MTT assay and colony formation assay were used to observe the effects of saponins and polysaccharides from Radix ranunculi ternati on in-vitro cultured human gastric cancer BGC823 cells. The results found that the saponins and polysaccharides from Radix Ranunculi Ternati had certain effects on both the growth and colony formation of human gastric cancer BGC823 cells, while improving the immune function of normal mice, of which saponins had more significant effects than polysaccharides.